Fajas oblicuas de deformación neotectónica en Precordillera y Cordillera Frontal (31° 30´ - 33° 30´ LS): controles paleotectónicos - Cortes, Jose Maria (2006)
The Southern Precordillera and Cerrilladas Pedemontanas of Mendoza, Argentina, are two major morphotectonic units in the eastern side of the Central Andes at 31º30' - 33º30' South latitude. There, two regional NW striking structures, called the Barreal - Las Peñas and Río Mendoza - Tupungato belts were developed as a consequence of gradual flattening of the Nazca plate in the last 20 M.yrs. Their orientation and complex structural geometry result from the interference of the Late Cenozoic Andean deformation with the NW-trending rift structure of the Triassic Cuyo basin and ancient collisional suture zones of Paleozoic age. This work demonstrates that paleotectonics features in the Triassic-Paleozoic substratum of the Southern Precordillera and the eastern margin of the Cordillera Frontal control the morphotectonic configuration and neotectonic structural distribution and rejuvenation of the Andes at these latitudes.